Decreased but persistent epigenetic age acceleration is associated with changes in T-cell subsets after initiation of highly active antiretroviral therapy in persons living with HIV - Sehl, Mary E.; Breen, Elizabeth Crabb; Shih, Roger; Li, Fengxue; Zhang, Joshua; Langfelder, Peter; Horvath, Steve; Bream, Jay H.; Duggal, Priya; Martinson, Jeremy; Wolinsky, Steven M.; Martinez-Maza, Otoniel; et al. (Frontiers in Bioinformatics, 2024)
Background: Persons living with HIV (PLWH) experience early onset of age-related illnesses, even in the setting of successful HIV suppression with highly active antiretroviral therapy (HAART). HIV infection is known to be associated with accelerated epigenetic aging as measured using DNA methylation (DNAm)-based estimates of biologic age and of telomere length (TL).Methods: DNAm levels (Infinium MethylationEPIC BeadChip) from peripheral blood mononuclear cells from 200 PLWH and 199 HIV seronegative participants (SN) matched on chronologic age, hepatitis C virus, and time intervals, were used to calculate epigenetic age acceleration, expressed as age-adjusted acceleration residuals from 4 epigenetic clocks [Horvath's pan-tissue (AAR), Extrinsic (EEAA), Phenotypic (PEAA), and Grim (GEAA)] plus age-adjusted DNAm-based TL (aaDNAmTL). Epigenetic age acceleration was compared for PLWH and SN at two visits: up to 1.5 years prior and 2-3 years after HAART (or equivalent visits). Flow cytometry was performed in PLWH and SN at both visits to evaluate T cell subsets.Results: Epigenetic age acceleration in PLWH decreased after initiation of HAART, but remains greater post-HAART compared to age-matched SN, with differences in medians of 6.6, 9.1, and 7.7 years for AAR, EEAA, and PEAA, respectively, and 0.39 units of aaDNAmTL shortening (all p<0.001). Cumulative HIV viral load after HAART initiation is associated with some epigenetic acceleration (EEAA, PEAA, aaDNAmTL), but even PLWH with undetectable HIV post-HAART show persistent epigenetic age acceleration compared to SN (p<0.001). AAR, EEAA, and aaDNAmTL showed significant associations with total, naïve, and senescent CD8 T cell counts; total CD4 T cell counts were associated with AAR, EEAA, and PEAA (p=0.04 to <0.001). In an epigenome-wide analysis using weighted gene co-methylation network analyses, 11 modules demonstrated significant DNAm differences pre-to post-HAART initiation. Of these, 9 were previously identified as significantly different from pre-to post-HIV infection, but in the opposite direction.In this large longitudinal study, we demonstrate that, although the magnitude of the difference decreases with HAART and is associated with cumulative viral load, PLWH are persistently epigenetically older than age-matched SN even after the successful initiation of HAART, and these changes are associated with changes in T cell subsets.